A serological survey for brucellosis in reindeer in Finnmark county, northern Norway - Åsbakk, Kjetil; Stuen, Snorre; Hansen, Hilde; Forbes, Lorry (Rangifer, 1999)
During September-December, 1990 to 1994, serum samples from a total of 5792 semi-domesticated reindeer (Rangifer tarandm tarandm) from Finnmark county, northern Norway, were screened for brucellosis on an indirect ELISA. There were no serologically positive animals. Twenty six of the animals had levels of antibodies detectable on the ELISA and were classed as suspicious, but the ELISA optical density readings were low compared to the readings for reindeer that were both culture positive and seropositive for Brucella suis biovar 4. When assayed on the standard tube agglutination test (STAT), all the 26 animals were seronegative. When absorbed with cells of Yersinia enterocolitica 0-9, the antibody detectable on the ELISA could be removed to a great extent from most of the sera, indicating previous or ongoing exposure to bacteria serologically cross-reacting with Brucella in these animals. We concluded that brucellosis was not present among reindeer in Finnmark during this study. This is supported by the absence of any reports of brucellosis among reindeer in Norway.